Transformasi Identitas Mahasiswa-Santri (Studi Fenomenologi Perubahan Identitas Mahasiswa STAIN Purwokerto Program 'Pesantrenisasi' Tahun Akademik 2013-2014) - Uus Uswatusolihah (IAIN Purwokerto, 2014)
Abstract: This study was aimed at knowing the transformation of identity amongstudents joining Pesantrenisasi Program in State College on Islamic Studies ofPurwokerto in the academic year 2013-2014. This study explored their own perceptionof being a student of the college and a santri. This is a qualitative research withinterviews as the main method of collecting data. A number of students wereinterviewed to get the answers of research questions. This research found thatpesantrenisasi program is successful in making closed relationship betweenstudent and pesantren (Islamic boarding school). The life in pesantren has madesome students transform their identity. The transformation happens gradually andslowly through unspontaneous self-dialogue. This transformation also gives them anew self-image, a new self-language, and new relationships with others as well asnew bounds with social norms. Before living in a pesantren, they imagine pesantrenas a dirty, massy, strict, and fully scheduled place of living. This image graduallychanges after they experience themselves living in pesantren. A new image comesto them that pesantren is an ideal place to study religious knowledge, to train aperson to be mature and having good character, and to perform more worship toGod. Some of the transformations include the quantity and quality of their worship aswell as their attitude and behavior to be more discipline, independent, and humble.Keywords: identity transformation, students, pesantren. Abstrak: Hasil penelitian ini adalah bahwa program pesantrenisasi telahberhasil mendekatkan mahasiswa dengan kehidupan pesantren dan menyebabkanterjadinya perubahan atau transformasi identitas diri sebagian mahasiswa.Transformasi itu sendiri pada umumnya berjalan secara perlahan dan melaluiproses-proses perenungan dan dialog diri yang tidak spontan. Transformasi jugamembuat mereka memperoleh citra diri yang baru, bahasa diri yang baru,hubungan-hubungan yang baru dengan orang-orang lain dan ikatan-ikatan yangbaru dengan tatanan sosial. Sebelum tinggal di pondok pesantren, mereka mendefinisikandunia pesantren adalah tempat yang kumuh, tidak rapi, memiliki banyakperaturan yang mengekang. Definisi ini berubah selama mereka berada di pesantren: Pondok pesantren adalah tempat yang ideal untuk menuntut berbagaiilmu agama, melatih diri menjadi lebih dewasa dan berkarakter yang baik sertamemperbanyak ibadah seraya mendekatkan diri kepada Allah SWT. Beberapaperubahan terjadi dalam kuantitas dan kualitas ibadah, perubahan dalam sikapdan perilaku yang lebih disiplin, mandiri dan sederhana, serta peningkatanpengetahuan berbagai ilmu agama Islam.Keywords: perubahan identitas, mahasiswa, pesantren.